2014
DOI: 10.1038/cddis.2014.262
|View full text |Cite
|
Sign up to set email alerts
|

The zinc sensing receptor, ZnR/GPR39, controls proliferation and differentiation of colonocytes and thereby tight junction formation in the colon

Abstract: The intestinal epithelium is a renewable tissue that requires precise balance between proliferation and differentiation, an essential process for the formation of a tightly sealed barrier. Zinc deficiency impairs the integrity of the intestinal epithelial barrier and is associated with ulcerative and diarrheal pathologies, but the mechanisms underlying the role of Zn2+ are not well understood. Here, we determined a role of the colonocytic Zn2+ sensing receptor, ZnR/GPR39, in mediating Zn2+-dependent signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 56 publications
(74 reference statements)
4
57
0
Order By: Relevance
“…Caco-2 colonocytic cells were grown in DMEM medium [20] containing 100 U ml -1 penicillin, 0.1 mg ml -1 streptomycin, 2 mM glutamine, 10% foetal calf serum (Biological Industries, Kibbutz Beit Haemek, Israel), 1% (v/v) nonessential amino acids (Biological Industries) and 2 mM sodium pyruvate (Sigma-Aldrich, Rehovot, Israel) in a 5% CO 2 humidified atmosphere at 378C. Fluorescent imaging measurements were acquired on cells loaded with Fura-2 acetoxymethyl ester (AM; TEF-Labs, Austin, TX, USA) in Ringer's solution (30 min 2.5 mM).…”
Section: Materials and Methods (A) Caco-2 Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Caco-2 colonocytic cells were grown in DMEM medium [20] containing 100 U ml -1 penicillin, 0.1 mg ml -1 streptomycin, 2 mM glutamine, 10% foetal calf serum (Biological Industries, Kibbutz Beit Haemek, Israel), 1% (v/v) nonessential amino acids (Biological Industries) and 2 mM sodium pyruvate (Sigma-Aldrich, Rehovot, Israel) in a 5% CO 2 humidified atmosphere at 378C. Fluorescent imaging measurements were acquired on cells loaded with Fura-2 acetoxymethyl ester (AM; TEF-Labs, Austin, TX, USA) in Ringer's solution (30 min 2.5 mM).…”
Section: Materials and Methods (A) Caco-2 Imagingmentioning
confidence: 99%
“…Cells were harvested into lysis buffer (50 mM HEPES, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 10% glycerol, 1% Triton X-100, 10 mM MgCl2, 25 mM NaF), in the presence of Protease Inhibitor Cocktail (1 : 50, Sigma-Aldrich). Protein concentrations were determined and whole-cell lysates (12 mg) were separated on 10% SDS-PAGE and blotted onto nitrocellulose membranes [20]. Antibodies raised against occludin (Invitrogen, Life Technologies) were used, and blots were quantified using IMAGEJ Gels Plugin.…”
Section: (B) Occludin Recovery In Caco-2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study of LY2784544, diarrhea, nausea, anemia, and transient increases in serum creatinine, uric acid, and potassium have been reported and attributed to a "typical tumor lysis syndrome" (Tefferi, 2012); however, it seems conceivable that at least some of these effects might be due to activation of GPR39. Interestingly, GPR39 is highly expressed in human colorectal adenocarcinoma HT-29 cells, and Zn 21 and a GPR39 agonist stimulated Gq signaling and promoted survival in these cells (Cohen et al, 2012(Cohen et al, , 2014Boehm et al, 2013). By using the fluorescent imaging plate reader assay, we have shown that GPR39-C3, LY2784544, and GSK2636771 strongly activate the Gq pathway in HT-29 cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GPR39 has been found to be expressed in mouse intestinal fibroblastlike cells (Zeng et al, 2012), human colon adenocarcinoma HT-29 cells (Yasuda et al, 2007;Cohen et al, 2012Cohen et al, , 2014, rat colon BRIN-BD11 cells (Moran et al, 2016), and mouse pancreatic epithelial NIT-1 cells (Fjellström et al, 2015). All of these cell types respond to Zn 21 via various signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%